The implications of household size and children for life-cycle saving - Bart Capéau; Bram De Rock (National Bank of Belgium, 2015)
On the basis of a concatenation of fifteen Belgian household budget surveys from 1995/96 to 2010, we investigate the impact of demographic factors, such as ageing and changing household composition, on saving behaviour. Not focusing on high frequency events (e.g. business cycles and unexpected shock), we find that saving behaviour is fundamentally driven by the change in household size and composition. Older people seem to be more impatient, and thus save less, though this evidence is not clear cut. Contrary to the usual practice of considering the allocation of household income over consumption and saving to be the result of one particular household's member decision, we present here a more individually based analysis of the data. By lack of true panel data, the assumptions that have to be made for such an approach (identical intertemporal preferences among household members) are severe, but not necessarily less preferable than those, if any, underlying the common practice of assuming one single individual decision maker.
Keywords: D14; D91; E21; 330; Saving; consumption; life-cycle; intertemporal choice; household demographics.; Privater Haushalt; Haushaltseinkommen; Sparquote; Kinder; Alternde Bevölkerung; Lebenszyklushypothese; Intertemporale Entscheidung; Belgien